The Influence of Wage System, Cost Efficiency, and Employee Motivation on Employee Work Productivity: An Empirical Study at PT Glory Industrial Semarang - Zamili, Tiwi Listiani; Maryani, Tri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the effect of the wage system, cost efficiency, and work motivation on employee productivity at PT Glory Industrial Semarang. The research method used is a quantitative approach with a survey technique. Data were collected through questionnaires distributed to 100 employees, with validity and reliability tests carried out to ensure data quality. Data analysis used multiple linear regression. The results showed that the wage system, cost efficiency, and work motivation each had a significant positive effect on employee productivity. Simultaneously, the three variables explained 94% of the variation in work productivity, with the wage system making the largest contribution. This shows that fair and proportional wages to the workload not only increase employee satisfaction and loyalty but also motivate them to work more optimally. Cost efficiency allows companies to provide incentives and facilities that support improved performance, while work motivation, both intrinsic, such as responsibility and desire to achieve, and extrinsic, such as awards and recognition, also strengthens employee commitment to company targets. This study has several limitations, including the fact that it was only conducted in one company, so the results cannot be generalized to other industries. In addition, this study used a cross-sectional approach, so it cannot capture long-term changes in the relationship of variables. Therefore, further research is recommended to expand the scope of the sample, consider additional variables such as organizational culture and leadership, and use a longitudinal approach to understand the dynamics of employee productivity changes over time.